2017
DOI: 10.12783/dteees/sses/icfse2016/10685
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Total Phenolic Compounds from a Brown Alga Hizikia Fusiformis

Abstract: Abstract. Screening of potential antibacterial activities of total phenolic compounds isolated from a brown alga Hizikia fusiformis (Hary.) Okam. was performed using two antibacterial assays. Significant differences were observed both in total phenolic contents and antibacterial activities of extracts from H. fusiformis collected along the coast of East China Sea and South China Sea against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Enterobacter aerogenes and Shewanella sp. Methanol extracts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Wu et al [ 98 ] investigated the antibacterial activity of H. fusiformis extract. In vitro studies of seaweed phenols showed that the methanolic extract of H. fusiformis from Zhoushan and Mazu, exhibited high antibacterial activity against E. coli .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [ 98 ] investigated the antibacterial activity of H. fusiformis extract. In vitro studies of seaweed phenols showed that the methanolic extract of H. fusiformis from Zhoushan and Mazu, exhibited high antibacterial activity against E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies of seaweed phenols showed that the methanolic extract of H. fusiformis from Zhoushan and Mazu, exhibited high antibacterial activity against E. coli . Furthermore, the ethanolic extract of H. fusiformis from Naozhou showed high antibacterial activity against B. subtilis [ 98 ]. However, it should be noted that the phenolic compositions of seaweeds is influenced by several factors, including genetic and environmental factors [ 100 ].…”
Section: Resultsmentioning
confidence: 99%